2016
DOI: 10.3109/02656736.2015.1119892
|View full text |Cite
|
Sign up to set email alerts
|

Thermal therapy of pancreatic tumours using endoluminal ultrasound: Parametric and patient-specific modelling

Abstract: Purpose To investigate endoluminal ultrasound applicator configurations for volumetric thermal ablation and hyperthermia of pancreatic tumors using 3D acoustic and biothermal finite element models. Materials and Methods Parametric studies compared endoluminal heating performance for varying applicator transducer configurations (planar, curvilinear-focused, or radial-diverging), frequencies (1–5 MHz), and anatomical conditions. Patient-specific pancreatic head and body tumor models were used to evaluate feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…In theoretical simulations of endoluminal ultrasound ablation of human pancreatic cancer, while pertaining to different anatomical conditions and tissue properties compared to porcine anatomy, it was demonstrated that endoluminal sonication through thinner luminal walls results in lower temperatures within the wall and minimizes the risk of thermal injuries. 31 As such, the risk of thermal damage would be reduced in humans due to the lower anticipated luminal wall thicknesses (2-3 mm). Similarly, in the experimental porcine setting there was likely an increased effective acoustic attenuation and absorption in the wall tissue due to the presence of food particles and/or gas bubbles in the mucosal layers, which could be reduced by flushing the interior stomach or GI lumen via lavage prior to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theoretical simulations of endoluminal ultrasound ablation of human pancreatic cancer, while pertaining to different anatomical conditions and tissue properties compared to porcine anatomy, it was demonstrated that endoluminal sonication through thinner luminal walls results in lower temperatures within the wall and minimizes the risk of thermal injuries. 31 As such, the risk of thermal damage would be reduced in humans due to the lower anticipated luminal wall thicknesses (2-3 mm). Similarly, in the experimental porcine setting there was likely an increased effective acoustic attenuation and absorption in the wall tissue due to the presence of food particles and/or gas bubbles in the mucosal layers, which could be reduced by flushing the interior stomach or GI lumen via lavage prior to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…17 Transducer design changes that would enable better sparing of thick luminal walls include incorporating more tightly focused designs, with the focus depth at least 1 cm beyond the wall tissue. 31 Improving coupling between the applicator cooling balloon and luminal wall through tip steering, compression, or fixation mechanisms may also provide for consistent or enhanced luminal sparing.…”
Section: Discussionmentioning
confidence: 99%
“…The acoustic and thermal material properties of each tissue that were incorporated in the simulations are listed in Table . Water cooling (25 °C) was modeled on the interior of the stomach luminal surface, by using a convective heat flux boundary equation with a heat transfer coefficient of h = 500 W/m 2 /°C . The stomach wall was modeled as 3 mm thick .…”
Section: Methodsmentioning
confidence: 99%
“…30,34,35 Water cooling (25°C) was modeled on the interior of the stomach luminal surface, by using a convective heat flux boundary equation with a heat transfer coefficient of h = 500 W/m 2 /°C. 35 The stomach wall was modeled as 3 mm thick. 36 Dirichlet boundary conditions constrained the outer borders of the tissue boundary to 37°C.…”
Section: F Simulated Temperature Distributions From Deployable Assmentioning
confidence: 99%
“…The acoustic properties of the pancreas were taken from [28]: density ¼ 1045 kg/m 3 , Thermal conductivity ¼ 0.51 W/m/ C, Specific Heat ¼ 3164 J/kg/ C, Perfusion rate¼ 4.5 kg/m 3 /s.…”
Section: Thermal Dose Simulationmentioning
confidence: 99%